2011
DOI: 10.1177/0886260510383038
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Animal Cruelty Methods and Their Link to Adult Interpersonal Violence

Abstract: Recent research has begun to establish a relationship between childhood acts of animal cruelty and later violence against humans. However, few studies have focused on the influence of animal cruelty methods on later interpersonal violence. In a replication of a study by Hensley and Tallichet (2009) and based on a sample of 180 inmates at medium- and maximum-security prisons in a Southern state, the present study examines the relationship between several retrospectively identified animal cruelty methods (drowne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
0
31
0
3
Order By: Relevance
“…Arluke, Levin, Luke, & Ascione, 1999;Ascione, 1999;Ascione, Thompson, & Black, 1997;Bucchieri, 2015;DeViney, Dickert, & Lockwood, 1983;Felthous, 1980;Felthous & Kellert, 1987a;Hellman & Blackman, 1966;Henderson, Hensley, & Tallichet, 2011;Hensley & Tallichet, 2008;Hensley & Tallichet, 2009;Hensley, Tallichet & Dutkiewicz, 2009;Hensley et al, 2012;Holoyda & Newman, 2016;Kellert & Felthous, 1985;Levitt, Hoffer, & Loper, 2016;Merz-Perez & Heide, 2003;MerzPerez, Heide, & Silverman, 2001;Miller & Knutson, 1997;Overton, Hensley & Tallichet, 2012;Tapia, 1971;Tallichet & Hensley, 2004;Walters, 2014). Whilst it is crucial to understand the relationship between childhood animal cruelty and later offending against humans, it is equally important to understand why people are cruel to animals to begin with.…”
Section: Animal Crueltymentioning
confidence: 99%
“…Arluke, Levin, Luke, & Ascione, 1999;Ascione, 1999;Ascione, Thompson, & Black, 1997;Bucchieri, 2015;DeViney, Dickert, & Lockwood, 1983;Felthous, 1980;Felthous & Kellert, 1987a;Hellman & Blackman, 1966;Henderson, Hensley, & Tallichet, 2011;Hensley & Tallichet, 2008;Hensley & Tallichet, 2009;Hensley, Tallichet & Dutkiewicz, 2009;Hensley et al, 2012;Holoyda & Newman, 2016;Kellert & Felthous, 1985;Levitt, Hoffer, & Loper, 2016;Merz-Perez & Heide, 2003;MerzPerez, Heide, & Silverman, 2001;Miller & Knutson, 1997;Overton, Hensley & Tallichet, 2012;Tapia, 1971;Tallichet & Hensley, 2004;Walters, 2014). Whilst it is crucial to understand the relationship between childhood animal cruelty and later offending against humans, it is equally important to understand why people are cruel to animals to begin with.…”
Section: Animal Crueltymentioning
confidence: 99%
“…Multiple studies have demonstrated that inmates who report a childhood history of bestiality are more likely to have been convicted of a personal crime such as rape, sexual assault, assault, and robbery and to have a greater number of personal crime convictions than subjects who denied a history of bestiality . When considered as a form of animal cruelty and compared to drowning, hitting, shooting, kicking, choking, or burning animals, bestiality was found to be the only form of cruelty that significantly predicted recurrent interpersonal violence among inmates . Research on juveniles suggests that those with a history of bestiality tend to report prior sexual offenses against humans and more offenses than sexual offenders of the same race and age without a history of bestiality .…”
Section: Casementioning
confidence: 99%
“…One driving force behind this change has been the affirmation of the link between animal abuse and various types of interpersonal violence, including child abuse, domestic violence, rape, robbery, and homicide. 31 Animal abuse at a young age appears to be predictive of later interpersonal violence, 19,37 and there is strong evidence that individuals are often violent toward animals and people concurrently. 5 Definitions of and criteria for animal abuse and neglect vary among jurisdictions, countries, and cultures.…”
Section: Introduction To Veterinary Forensicsmentioning
confidence: 99%